Andrographolide nanophytosomes exhibit enhanced cellular delivery and pro-apoptotic activities in HepG2 liver cancer cells. (31st December 2023) - Neamatallah, Thikryat; Malebari, Azizah M.; Alamoudi, Abdulmohsin J.; Nazreen, Syed; Alam, Mohammad Mahboob; Bin-Melaih, Hawazen H.; Abuzinadah, Osama A.; Badr-Eldin, Shaimaa M.; Alhassani, Gharam; Makki, Lamar; Nasrullah, Mohammed Z.
Abstract: Andrographolide (AG), a major active constituent of Andrographis paniculata, is known to hinder proliferation of several types of cancer cells. However, its poor solubility and cellular permeability restrict its use in clinical applications. In this study, AG-loaded phytosomes (AG-PTMs) were formulated and optimized with respect to particle size using l -α-phosphatidylcholine (PC):AG ratio and sonication time (ST) as independent variables. The optimized formula was prepared at 1:2.7 for AG:PC molar ratio and 4.9 min for ST and exhibited a particle size of 243.7 ± 7.3 nm, polydispersity index (PDI) of 0.310 and entrapment efficiency of 72.20 ± 4.53. Also, the prepared formula showed a slow release of AG over 24-h period. The antiproliferative activity of AG-PTMs was investigated against the liver cancer cell line HepG2. AG-PTMs significantly repressed the growth of HepG2 cells with an IC50 value of 4.02 ± 0.14 µM. AG uptake by HepG2 cells was significantly enhanced in incubations containing the optimized formula. AG-PTMs also caused G2-M cell cycle phase arrest and increased the fraction of apoptotic cells in pre-G1 phase. These effects were associated with induction of oxidative stress and mitochondrial dysfunction. In addition, AG-PTMs significantly upregulated mRNA expression of BAX and downregulated that of BCL2. Furthermore, AG-PTMs significantly enhanced the concentration of caspase-3 in comparison to raw AG. These data indicate that the phytosomal delivery of AG significantly inhibited HepG2 cell proliferation through enhanced cellular uptake, arresting cell cycle at the G2-M phase and inducing mitochondrial-dependent apoptosis.